Design of Efficient and Safe Neural Stimulators A Multidisciplinary Approach - van Dongen, Marijn; Serdijn, Wouter; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book discusses the design of neural stimulator systems which are used for the treatment of a wide variety of brain disorders such as Parkinson's, depression and tinnitus. Whereas many existing books treating neural stimulation focus on one particular design aspect, such as the electrical design of the stimulator, this book uses a multidisciplinary approach: by combining the fields of neuroscience, electrophysiology and electrical engineering a thorough understanding of the complete neural stimulation chain is created (from the stimulation IC down to the neural cell). This multidisciplinary approach enables readers to gain new insights into stimulator design, while context is provided by presenting innovative design examples. Provides a single-source, multidisciplinary reference to the field of neural stimulation, bridging an important knowledge gap among the fields of bioelectricity, neuroscience, neuroengineering and microelectronics;Uses a top-down approach to understanding the neural activation process: from electrode modeling to cell activation; Discusses the mechanisms leading to neural damage and considers several strategies for electrochemical balance; Describes novel, high frequency stimulation principles that take a fundamentally different approach, compared to existing stimulator designs.
Introduction -- Modeling the activation of Neural cells -- Electrode-tissue interface during a stimulation cycle -- Efficacy of high frequency switched-mode neural stimulation -- System design of neural stimulators -- Design of an arbitrary waveform charge balanced stimulator -- Switched-mode High Frequency Stimulator Design -- Conclusions.
Keywords: Electronic circuits; Biomedical engineering; Electronics; Electronic Circuits and Systems; Biomedical Engineering and Bioengineering; Electronics and Microelectronics, Instrumentation